Effect of Metakaolin Developed from Local Soorh on Fresh Properties and Compressive Strength of Self-Compacted Concrete - Saand, A.; Jamali, K. A.; Keerio, M. A.; Ali, T.; Bhatti, N. (Engineering, Technology & Applied Science Research, 2019)
This paper presents the fresh properties of Self-Compacting Concrete (SCC) containing metakaolin (MK) produced by calcination of the natural material soorh of district Thatta Sind in Pakistan. Five mixes were tested, including four MK mixes replacing 5-20% of cement, with 0.38 water/binder (W/B) ratio. The fresh properties of the SCCs were evaluated using slump flow, T50, V-funnel, J ring, L-box and sieve segregation tests. Compressive strength of the control and the MK SCC was also investigated. The fresh concrete test results revealed that SCC could be developed by substituting cement with local MK, using 2% superplasticizers and without using a viscosity-modifying amplifier. The SCC with 15% replacement of cement with local MK showed maximum compressive strength, which was 10.39% higher than the control specimen’s without MK.